Nickel-based nitrogen-doped carbon material and preparation method and application thereof

By using nickel-based nitrogen-doped carbon material as a catalyst, the problems of high thermal energy consumption and poor catalyst stability of alcohol amine solution are solved, and high-efficiency and low-energy consumption of CO2 desorption and regeneration are achieved, reducing carbon capture costs.

CN119215958APending Publication Date: 2024-12-31NORTH CHINA ELECTRIC POWER UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411579487.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the existing carbon capture technology, the regeneration heat energy consumption of alcohol amine solution is high, resulting in high carbon capture cost. The existing solid acid catalysts have poor stability in high temperature and strong alkali environments, making it difficult to control the protection of active components.

Method used

Nickel-based nitrogen-doped carbon material is used as a catalyst, and prepared by mixing the nitrogen-containing carbon source and nickel source and calcining it to form a stable acidic site and a catalyst that is resistant to high temperature and alkaline environment, which is used to accelerate the desorption and regeneration of CO2.

Benefits of technology

The CO2 desorption rate and amount are significantly improved, the desorption energy consumption is reduced, the catalyst operation life is extended, and the regeneration heat load of the alcohol amine solution is reduced, achieving low-energy carbon capture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215958A_ABST
    Figure CN119215958A_ABST
Patent Text Reader

Abstract

The invention provides a nickel-based nitrogen-doped carbon material as well as a preparation method and application thereof, and relates to the technical field of catalytic materials. The preparation method of the nickel-based nitrogen-doped carbon material provided by the invention comprises the following steps: mixing a nitrogen-containing carbon source, a nickel source and water, and carrying out solid-liquid separation to obtain a complex; and calcining the complex to obtain the nickel-based nitrogen-doped carbon material. The prepared nickel-based nitrogen-doped carbon material catalyst is high in activity and high in tolerance to high-temperature and strong-alkali environments, and the service life of the catalyst can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a nickel-based nitrogen-doped carbon material and a preparation method and application thereof. Background Art

[0002] my country's CO2 emissions are as high as 10.5 billion tons per year, ranking first in the world. From the perspective of industry and energy structure, the power industry is the most important field of carbon emissions in my country. Among the typical carbon capture devices currently in use, the post-combustion CO2 capture process is the most widely used and the technology is the most mature. This carbon capture technology mostly uses alcohol amines and other chemical absorbents to separate the CO2 in the gas at the end of the coal-fired flue gas emission. It has technical advantages such as fast absorption rate, large absorption capacity, and the ability to handle large-scale industrial flue gas. After the alcohol amine solution absorbs CO2 to saturation, it will generate a stable absorption product, carbamate (MEACOO - ) and protonated amines (MEAH + ), such absorption products are very stable, so in order to achieve the reuse of alcohol amines to reduce the operating cost of carbon capture, CO2 must be released again from the saturated alcohol amine solution. - It is very stable, and a large amount of high-quality steam is required to achieve efficient regeneration of the absorbent, resulting in the desorption energy consumption of saturated amine absorbent as high as 3.6-4.0GJ / t CO2, and the operating cost of carbon capture as high as 400-600 yuan / t CO2. Therefore, the development of advanced low-energy CO2 desorption technology is a bottleneck problem that needs to be solved in carbon capture technology using alcohol amine solution as absorbent.

[0003] The heat energy required for the regeneration of saturated alcohol amine absorbent accounts for more than 70% of the energy consumption of the entire carbon capture process. In order to reduce the regeneration heat load of the saturated amine solution, the simplest and most economical method is to accelerate the desorption and regeneration rate of CO2 through a solid acid catalyst. This method is expected to reduce the regeneration energy consumption, slow down the degradation of the amine solution and the corrosion of the equipment, and significantly reduce the operating cost of the CO2 capture device.

[0004] According to literature reports, solid acid catalysts generally used for catalytic CO2 desorption are mainly divided into four categories: metal oxides, sulfated metal oxides, molecular sieves, and composite solid acid catalysts. This type of catalyst is called solid acid mainly because it has a large amount of L acid and B acid on its surface. Specifically: In the desorption reaction, B acid can be MEACOO - Provide available protons; L acid stretching MEACOO -CN bonds, accelerating the desorption of CO2; under the joint action of B acid and L acid, the energy consumption of the desorption system is greatly reduced. Metal oxide or sulfated metal oxide solid acid catalysts have the problem of poor stability, especially metals are extremely easy to dissolve in high temperature and strong alkaline environment. Metal ions enter the absorption end with the absorbent circulation and contact oxygen, causing a large amount of degradation of the absorbent. Molecular sieves and composite solid acid catalysts have defects such as easy pore blockage, resulting in poor catalyst stability, easy deactivation and regeneration difficulties. In general, the activity of existing catalysts still needs to be improved, there is a lack of effective control means for the protection of the active components of the desorption catalyst, and the stability of solid acid catalysts under high temperature and alkaline conditions also needs to be improved. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a nickel-based nitrogen-doped carbon material and a preparation method and application thereof. The nickel-based nitrogen-doped carbon material catalyst prepared by the present invention has high activity and strong tolerance to high temperature and strong alkaline environment, and can increase the operating life of the catalyst.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a nickel-based nitrogen-doped carbon material, comprising the following steps:

[0008] The nitrogen-containing carbon source, the nickel source and water are mixed, and after solid-liquid separation, a composite is obtained;

[0009] The composite is calcined to obtain a nickel-based nitrogen-doped carbon material.

[0010] Preferably, the nitrogen-containing carbon source comprises a nitrogen-containing organic polymer.

[0011] Preferably, the nitrogen-containing carbon source includes a product formed from 2,4,6-triformylphloroglucinol and 4-nitro-1,3-phenylenediamine, a product formed from trimesaldehyde and meta-phenylenediamine, or a product formed from melamine and cyanuric acid.

[0012] Preferably, the nickel source is a nickel salt.

[0013] Preferably, the calcination temperature is 500-700° C., and the holding time is 2-4 hours.

[0014] Preferably, the calcination is carried out under a protective atmosphere.

[0015] The present invention provides a nickel-based nitrogen-doped carbon material prepared by the preparation method described in the above technical solution.

[0016] The present invention provides the application of the nickel-based nitrogen-doped carbon material described in the above technical solution in the field of catalysis.

[0017] The present invention provides the use of the nickel-based nitrogen-doped carbon material described in the above technical solution in catalyzing the desorption of carbon dioxide.

[0018] Preferably, the desorption temperature is 90-110°C.

[0019] The nickel-based nitrogen-doped carbon material prepared by the present invention has a regular nitrogen-doped carbon layer structure, and forms a stable acid site (including In addition, the tri-coordinate and tetra-coordinate structures formed by the nitrogen atoms on the surface of the nickel-based nitrogen-doped carbon material and nickel can also enhance the stability of the catalyst and improve its tolerance to harsh environments such as high temperature and alkalinity. After testing, it was found that after multiple desorption runs, the residual nickel element in the solution was trace.

[0020] The present invention forms a stable coordination structure with nickel through the highly dispersed nitrogen atoms on the surface of the carbon layer, and achieves excellent catalytic CO2 desorption performance at 90°C. The maximum CO2 desorption rate is 24.69 mmol / min, which is 285.76% of the maximum CO2 desorption rate under blank conditions, and the CO2 desorption amount within 30 minutes is as high as 343.51 mmol. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 TEM morphology and element distribution of Ni / NC-600;

[0022] Figure 2 is the XRD diffraction result of Ni / NC-600;

[0023] Figure 3 Py-IR test results of Ni / NC-600;

[0024] Figure 4 is the Raman spectrum of Ni / NC-600;

[0025] Figure 5 XPS analysis of Ni / NC-500, Ni / NC-600 and Ni / NC-700;

[0026] Figure 6 It is a schematic diagram of the CO2 desorption performance test device;

[0027] Figure 7 is the desorption rate of the catalyst under non-catalytic conditions and before and after calcination;

[0028] Figure 8 The desorption amount change curve of the catalyst under non-catalytic conditions and before and after calcination;

[0029] Fig. 9is the desorption rate of Ni / NC-500, Ni / NC-600 and Ni / NC-700;

[0030] Fig.10 Comparison of the desorption performance of nickel-based nitrogen-doped carbon materials prepared from different nitrogen-containing organic polymers. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a nickel-based nitrogen-doped carbon material, comprising the following steps:

[0032] The nitrogen-containing carbon source, the nickel source and water are mixed, and after solid-liquid separation, a composite is obtained;

[0033] The composite is calcined to obtain a nickel-based nitrogen-doped carbon material.

[0034] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0035] The present invention mixes a nitrogen-containing carbon source, a nickel source and water, and obtains a composite after solid-liquid separation. In the present invention, the nitrogen-containing carbon source preferably includes a nitrogen-containing organic polymer, and more preferably includes a product formed by 2,4,6-triformylphloroglucinol and 4-nitro-1,3-phenylenediamine, a product formed by trimesaldehyde and metaphenylenediamine, or a product formed by melamine and cyanuric acid.

[0036] In the present invention, the preparation method of the product formed by 2,4,6-triformyl phloroglucinol and 4-nitro-1,3-phenylenediamine preferably comprises: mixing 2,4,6-triformyl phloroglucinol, 4-nitro-1,3-phenylenediamine and 1,4-dioxane, adding an acetic acid aqueous solution to obtain a suspension; subjecting the suspension to a solvent thermal reaction to obtain a nitrogen-containing organic polymer. In the present invention, the molar ratio of 2,4,6-triformyl phloroglucinol and 4-nitro-1,3-phenylenediamine is preferably 1 to 3:3, more preferably 2:3. In the present invention, the dosage ratio of 2,4,6-triformyl phloroglucinol and 1,4-dioxane is preferably 2 mmol to 6 mmol: 25 mL, more preferably 4 mmol: 25 mL. In the present invention, the volume ratio of 1,4-dioxane and acetic acid aqueous solution is preferably 25:1-3, more preferably 25:2; the concentration of the acetic acid aqueous solution is preferably 1-5 mol / L, more preferably 3 mol / L. In the present invention, the mixing of 2,4,6-triformylphloroglucinol, 4-nitro-1,3-phenylenediamine and 1,4-dioxane preferably includes ultrasonic oscillation for 10 minutes. The present invention preferably ultrasonically oscillates for 5 minutes after adding acetic acid aqueous solution. In the present invention, the suspension is orange-yellow. In the present invention, the temperature of the solvent thermal reaction is preferably 110-130°C, more preferably 120°C; the time of the solvent thermal reaction is preferably 48-96h, more preferably 72h. In the present invention, after the solvent thermal reaction, the obtained solid powder is preferably washed and dried in sequence. In the present invention, the solid powder is yellow. In the present invention, the washing liquid used for the washing is preferably anhydrous ethanol; the number of washing times is preferably 3 times; the drying temperature is preferably 50° C., the drying time is preferably 4 hours; and the drying is preferably vacuum drying.

[0037] In the present invention, the preparation method of the product formed by trimesic acid and m-phenylenediamine is basically the same as the preparation method of the product formed by 2,4,6-triformylphloroglucinol and 4-nitro-1,3-phenylenediamine, the only difference is that the raw materials are adjusted to trimesic acid and m-phenylenediamine, which will not be repeated here.

[0038] In the present invention, the preparation method of the product formed by melamine and cyanuric acid preferably comprises: mixing melamine, cyanuric acid and water, and obtaining solid powder by solid-liquid separation; washing and drying the solid powder in sequence to obtain a nitrogen-containing organic polymer. In the present invention, the molar ratio of melamine to cyanuric acid is preferably 1:1; the dosage ratio of melamine to water is preferably 4mmol:45mL; and the water is preferably deionized water. In the present invention, the mixing is preferably stirring; the mixing time is preferably 15 hours; and the mixing temperature is preferably room temperature. In the present invention, the solid-liquid separation is preferably suction filtration. In the present invention, the washing liquid used for washing is preferably deionized water; and the number of washings is preferably 3 times. In the present invention, the drying temperature is preferably 50°C, the drying time is preferably 4h; and the drying is preferably vacuum drying.

[0039] In the present invention, the nickel source is preferably a nickel salt, more preferably nickel acetate tetrahydrate or nickel chloride. In the present invention, the mass ratio of the nitrogen-containing carbon source to the nickel source is preferably 0.5g:0.05-0.2g, more preferably 0.5g:0.1g.

[0040] In the present invention, the water is preferably deionized water. In the present invention, the usage ratio of the nitrogen-containing carbon source to water is preferably 0.5 g: 20-60 mL, more preferably 0.5 g: 40 mL.

[0041] In the present invention, the nitrogen-containing carbon source, the nickel source and the water are preferably mixed at room temperature; the mixing is preferably carried out under stirring; and the mixing time is preferably 4 hours. During the mixing process of the present invention, the nickel salt dissolved in the water forms a coordination structure with the nitrogen atoms on the surface of the nitrogen-containing carbon source, so that the nickel element is stably loaded on the surface of the carbon material.

[0042] In the present invention, the solid-liquid separation is preferably performed by suction filtration.

[0043] In the present invention, the solid obtained after the solid-liquid separation is preferably dried to obtain a composite. In the present invention, the drying temperature is preferably 80° C. and the drying time is preferably 4 hours.

[0044] After obtaining the complex, the present invention calcines the complex to obtain a nickel-based nitrogen-doped carbon material. In the present invention, the calcination temperature is preferably 500-700°C, more preferably 600°C; the heating rate is preferably 2°C / min; the holding time is preferably 2-4h, more preferably 3h. In the present invention, the calcination is preferably carried out under a protective atmosphere, more preferably an argon atmosphere. In the present invention, the calcination is preferably carried out in a tube furnace. The present invention preferably cools naturally after the calcination to obtain a nickel-based nitrogen-doped carbon material. In the present invention, the nickel-based nitrogen-doped carbon material is a black solid. The present invention will form a certain graphitized carbon layer material after calcination, and the nitrogen atoms and nickel ions form a more stable three-coordinate and / or four-coordinate structure.

[0045] The present invention provides a nickel-based nitrogen-doped carbon material prepared by the preparation method described in the above technical solution. In the present invention, the nickel-based nitrogen-doped carbon material includes a nitrogen-doped carbon material and a nickel element loaded on the nitrogen-doped carbon material. In the present invention, the nitrogen-doped carbon material is preferably a layered structure. In a specific embodiment of the present invention, the nickel element is divalent metal nickel. In the present invention, the form of the nickel element is preferably nanoclusters and / or single atoms. In the present invention, the mass content of the nickel element in the nickel-based nitrogen-doped carbon material is preferably 0.4-0.6%, more preferably 0.5-0.6%; the mass content of the nitrogen element is preferably 4-15%.

[0046] The present invention provides the application of the nickel-based nitrogen-doped carbon material described in the above technical solution in the field of catalysis. The present invention preferably applies the nickel-based nitrogen-doped carbon material to catalytic desorption and regeneration of saturated alcohol amine absorbent. In the present invention, the nickel-based nitrogen-doped carbon material is a solid acid catalyst.

[0047] The present invention provides the use of the nickel-based nitrogen-doped carbon material described in the above technical solution in catalyzing the desorption of carbon dioxide, preferably used in the desorption of CO2 in an alcohol amine absorption system. In the present invention, the desorption temperature is preferably 90 to 110°C. In the present invention, the nickel-based nitrogen-doped carbon material is added to a saturated ethanolamine aqueous solution to desorb CO2. In a specific embodiment of the present invention, the saturated ethanolamine aqueous solution is an ethanolamine aqueous solution that absorbs CO2 to saturation. In the present invention, the pH value of the saturated ethanolamine aqueous solution is preferably 12. The present invention can increase the desorption rate of CO2 and realize an efficient and low-energy alcohol amine regeneration technology.

[0048] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] The chemical reagents used in the examples were purchased from Aladdin Reagent Company and were of analytical grade.

[0050] Example 1

[0051] 4 mmol of 2,4,6-triformylphloroglucinol and 6 mmol of 4-nitro-1,3-phenylenediamine were dissolved in 25 mL of 1,4-dioxane and ultrasonically vibrated for 10 min; 2 mL of acetic acid aqueous solution (the concentration of acetic acid aqueous solution is 3 mol / L) was dropped into it, and ultrasonic vibration was continued for 5 min to obtain an orange-yellow suspension; then, the orange-yellow suspension was poured into the Teflon liner of the reactor, and the reactor was sealed and heated to 120° C. and reacted for 72 hours; the obtained reaction system was filtered to obtain a yellow solid powder; the yellow solid powder was washed with anhydrous ethanol for 3 times, and vacuum dried at 50° C. for 4 hours to obtain a nitrogen-containing organic polymer.

[0052] 0.5 g of the nitrogen-containing organic polymer and 0.1 g of nickel acetate tetrahydrate were dispersed in 40 mL of deionized water, stirred at room temperature for 4 h, and then filtered. The obtained solid was dried (drying temperature was 80° C., and drying time was 4 h) and named Ni@NC-uncalcined;

[0053] The Ni@NC-uncalcined was placed in a tube furnace, heated to 600°C at a heating rate of 2°C / min under an argon atmosphere, calcined at 600°C for 3h, and naturally cooled to obtain a black solid powder, i.e., a nickel-based nitrogen-doped carbon material, named Ni / NC-600.

[0054] Example 2

[0055] The preparation method is basically the same as that of Example 1, except that the calcination temperature is adjusted from "600°C" to "500°C", and the obtained nickel-based nitrogen-doped carbon material is named Ni / NC-500.

[0056] Example 3

[0057] The preparation method is basically the same as that of Example 1, except that the calcination temperature is adjusted from "600°C" to "700°C", and the obtained nickel-based nitrogen-doped carbon material is named Ni / NC-700.

[0058] Example 4

[0059] The preparation method is basically the same as that in Example 1, except that the preparation method of the nitrogen-containing organic polymer is adjusted as follows: 4 mmol of trimesaldehyde and 6 mmol of m-phenylenediamine are dissolved in 25 mL of 1,4-dioxane, and ultrasonically shaken for 10 min; 2 mL of acetic acid aqueous solution (the concentration of the acetic acid aqueous solution is 3 mol / L) is dropped, and ultrasonically shaken for 5 min to obtain a brown suspension; then, the brown suspension is poured into the Teflon liner of the reactor, and the reactor is sealed and heated to 120° C., and reacted for 72 hours; the obtained reaction system is filtered to obtain a brown solid powder; the brown solid powder is washed with anhydrous ethanol 3 times, and vacuum dried at 50° C. for 4 h to obtain a nitrogen-containing organic polymer.

[0060] The nickel-based nitrogen-doped carbon material prepared in this example is named Ni / NC-(1)-600.

[0061] Example 5

[0062] The preparation method is basically the same as that in Example 1, except that the preparation method of the nitrogen-containing organic polymer is adjusted as follows: 4 mmol of melamine and 4 mmol of cyanuric acid are dispersed in 45 mL of deionized water and stirred for 15 hours; the white solid powder obtained by filtration is washed three times with deionized water and vacuum dried at 50° C. for 4 hours to obtain a nitrogen-containing organic polymer.

[0063] The nickel-based nitrogen-doped carbon material prepared in this example is named Ni / NC-(2)-600.

[0064] Test Example 1

[0065] The transmission electron microscopy (TEM) results of Ni / NC-600 are as follows Figure 1 As shown, nickel is highly dispersed on the surface of the carrier (nitrogen-doped carbon material). It can be inferred that nickel forms a stable coordination structure with a large number of nitrogen atoms on the surface of the carrier, and nickel is highly dispersed on the surface of the carbon layer in the form of single atoms and nanoclusters.

[0066] The X-ray diffraction (XRD) results of Ni / NC-600 are as follows Figure 2 As shown in the figure, an obvious diffraction peak appears near 2θ=21.5°, which is located to the left, with a wide peak shape and weak intensity, corresponding to the typical 101 peak position of carbon materials, and close to the diffraction peak position of graphite, indicating that the material is mainly lamellar carbon material, and the integrity of the crystal structure decreases and the disorder increases due to interlayer peeling.

[0067] The acidity of Ni / NC-600 at 40℃, 90℃ and 150℃ was obtained by pyridine infrared (Py-IR) test. The data are as follows: Figure 3 Shown: 1452cm -1and 1612cm -1 The peak position represents the L acid site, 1492 cm -1 The peak at 1542 cm represents the mixed acidity of L acid and B acid. -1 The peak position represents the B acid site. By increasing the test temperature, it can be seen that the L acid site of Ni / NC-600 is at 1452cm -1 The peak at 1612cm -1 The peak of showed a trend of increasing first and then weakening, while the B acid site had no obvious change. Through quantitative testing of the acid sites of the material, the results showed that at 90°C, the L acid and B acid sites of Ni / NC-600 were 22.68μmol / g and 1.75μmol / g, respectively, which were better than other carbon material solid acid catalysts.

[0068] The Raman spectrometer (Raman) test results of Ni / NC-600 are as follows Figure 4 As shown in the figure, 1357cm -1 and 1566cm -1 The two absorption peaks correspond to the disordered structure near the edge of the microcrystal structure (sp 3 vibration mode, D band) and the ordered structure of the graphene layer plane (sp 2 vibration mode, G band). Figure 4 The peaks of band D and band G were integrated, and the results showed that the ratio of the peak areas (I D / I G ) is 2.13, which indicates that Ni / NC-600 presents a structure dominated by disordered carbon after calcination.

[0069] The X-ray photoelectron spectroscopy (XPS) test results of Ni / NC-500, Ni / NC-600 and Ni / NC-700 are as follows: Figure 5 As shown. The XPS total spectra of the three materials all contain a small amount of Ni element. In the C spectrum, clear CN, C=N and CC / C=C can be analyzed, which is consistent with the results of the above Raman spectrum, confirming the carbon layer structure in the calcined material. In addition, the N spectrum can be divided into oxidized N, graphitic N, pyrrolic N and pyridinic N according to different bonding positions, and there is a very small amount of Ni-N, which indicates that a small amount of Ni forms a coordination bond with N. Especially in the Ni / NC-600 material, the content of pyridinic N is relatively small, and with the decrease of calcination temperature, there is a trend of pyrrolic N shifting to the right and pyridinic N shifting to the left.

[0070] Test Example 2

[0071] The CO2 desorption performance testing device assembled with magnetic stirring and constant temperature oil bath pot used in the present invention is as follows Figure 6The device is used to evaluate the catalytic activity of the catalyst in promoting the desorption rate of CO2 at a certain temperature. The specific steps are as follows: First, 200 mL of ethanolamine aqueous solution (MEA aqueous solution, concentration of 5 mol / L) is placed in a round-bottom flask, and 200 mL / min of pure CO2 is introduced at room temperature until the MEA aqueous solution reaches saturation and the absorption product is carbamate (MEACOO - ); then, add 0.1g of catalyst (nickel-based nitrogen-doped carbon material prepared in Example) into the round-bottom flask, turn on the oil bath heating switch until the solution temperature in the round-bottom flask is 90°C; during the entire heating process, the instantaneous desorption rate of CO2 at the outlet of the round-bottom flask is analyzed by a flow meter to compare and evaluate the performance of the catalyst. During the entire absorption and desorption process, circulating condensed water is used to reduce the gas temperature at the outlet of the round-bottom flask, avoid the loss caused by the volatilization of the MEA aqueous solution during the heating process, and reduce the impact of the volatile gas on the detector.

[0072] (1) First, the desorption performance of the catalysts was tested under non-catalytic conditions and before and after calcination. Figure 7 As shown. Among them, the CO2 desorption rate under Ni / NC-600 catalysis reached 24.69mmol / min in 17min, at this time, the catalytic rate of Ni@NC-uncalcined was 9.22mmol / min, and the non-catalytic blank desorption (without adding catalyst, Blank) rate was 2.28mmol / min. In terms of the comparison of the highest desorption rate, the highest desorption rate of Ni@NC-uncalcined was 12.69mmol / min, and Ni / NC-600 showed the best desorption performance, and its highest desorption rate was 285.76% of the highest desorption rate under blank conditions. Therefore, Ni / NC-600 showed the best catalytic desorption performance. This may be because compared with the uncalcined Ni@NC, the calcined Ni / NC-600 forms a relatively regular carbon layer, and the periodic pyridinic nitrogen and pyrrolic nitrogen are more easily coordinated with nickel ions to form efficient acid sites. Combined with the above-mentioned pyridine infrared test results, under the desorption conditions of 90°C, Ni / NC-600 has abundant L acid and B acid sites, which is beneficial to promote the proton circulation rate of the saturated MEA desorption system under heating conditions, thereby accelerating the desorption rate of CO2.

[0073] (2) Figure 8The changes of CO2 desorption under three conditions over time were compared. When the desorption reaction was carried out to 30 minutes, the desorption under Ni / NC-600 catalysis was 343.51mmol, the desorption under Ni@NC-uncalcined was 154.56mmol, and the desorption under the blank condition (no catalyst added, Blank) was only 42.16mmol. At this time, the desorption under Ni / NC-600 catalysis within 30 minutes was more than 8 times the blank desorption. Therefore, Ni / NC-600 can increase the desorption rate of CO2 at the same desorption temperature, and significantly increase the desorption amount of CO2. That is to say, in actual industrial carbon capture, the catalytic desorption technology based on Ni / NC-600 can improve the desorption efficiency of CO2 and reduce the loading amount of alcohol amine, thereby reducing the amount of absorbent without changing the amount of flue gas captured by carbon, or reducing the residence time of the absorbent, so as to achieve the purpose of reducing operating energy consumption.

[0074] (3) Performance comparison at different calcination temperatures

[0075] Comparison of Ni / NC-500, Ni / NC-700 and Ni / NC-600 shows the performance of the three nickel-based nitrogen-doped carbon materials. Fig. 9 As shown, Fig. 9 Blank in the table indicates blank desorption without adding catalyst. The highest CO2 desorption rates of Ni / NC-500 and Ni / NC-700 were 15.91mmol / min and 18.45mmol / min, respectively, which were both lower than 24.69mmol / min under Ni / NC-600 catalysis. Therefore, 600℃ is the optimal preparation condition for nickel-based nitrogen-doped carbon materials. At this calcination temperature, it is easier to form efficient active sites and achieve optimal catalytic performance.

[0076] (4) The present invention compares the catalytic performance of three different nitrogen-containing organic polymers loaded with nickel and calcined. The nitrogen-containing organic polymers are respectively the product formed by 2,4,6-triformylphloroglucinol and 4-nitro-1,3-phenylenediamine (the corresponding material is Ni / NC-600), the product formed by trimesic acid and m-phenylenediamine (the corresponding material is Ni / NC-(1)-600), and the product formed by melamine and cyanuric acid (the corresponding material is Ni / NC-(2)-600). The performance results are as follows: Fig.10As shown, the product formed by 2,4,6-triformylphloroglucinol and 4-nitro-1,3-phenylenediamine showed a higher desorption rate because it contained more nitrogen source. The highest CO2 desorption rates of Ni / NC-(1)-600 and Ni / NC-(2)-600 were 16.15mmol / min and 12.34mmol / min, respectively, while the highest desorption rate of blank condition (no catalyst added, Blank) was 8.64mmol / min. Therefore, the nickel-based nitrogen-doped carbon material prepared by the present invention has good catalytic performance and is technologically advanced.

[0077] Test Example 3

[0078] Table 1 Summary of the properties of Ni / NC-600 prepared in the literature and Example 1

[0079]

[0080] In Table 1, the increase in desorption rate refers to the ratio of the maximum desorption rate of CO2 under catalyst catalysis to the maximum desorption rate of CO2 under blank conditions (without adding catalyst) using the CO2 desorption performance test method of Test Example 2.

[0081] [1] L.

[0082] [2]Xing, L.; Wei, K.; Li, Q.; Wang, R.; Zhang, S.; Wang, L., One-stepsynthesizedSO4 2- / ZrO2-HZSM-5 solid acid catalyst for carbamate decomposition inCO2 capture.Environ.Sci.Technol.2020,54,13944-13952.

[0083] [3]Xing,L.;Wei,K.;Li,Y.;Fang,Z.;Li,Q.;Qi,T.;An,S.;Zhang,S.;Wang,L.,TiO2 coating strategy for robust catalysis of the metal-organic frameworktowardenergy-efficient CO2 capture.Environ.Sci.Technol.2021,55,11216-11224.

[0084] [4]Gao,H.;Huang,Y.;Zhang,X.;Bairq,Z.A.S.;Huang,Y.;Tontiwachwuthikul,P.;Liang,Z.,Catalytic performance and mechanism ofSO4 2- / ZrO2 / SBA-15 catalystfor CO2 desorption in CO2-loaded monoethanolaminesolution.Appl.Energy.2020,259,114179.

[0085] [5]Bhatti,U.H.;Shah,A.K.;Hussain,A.;Khan,H.A.;Park,C.Y.;Nam,S.C.;Baek,I.H.,Catalytic activity of facilely synthesized mesoporous HZSM-5catalystsfor optimizing the CO2 desorption rate from CO2-rich aminesolutions.Chem.Eng.J.2020,389.

[0086] [6]Bairq,Z.A.S.,Gao,H.,Murshed,F.A.M.,Tontiwachwuthikul,P.&Liang,Z.Modified heterogeneous catalyst-aided regeneration of co2 capture amines:apromising perspective for a drastic reduction in energy consumption.ACSSustain.Chem.Eng.2020,8,9526-9536.

[0087] [7]Bhatti,U.H.;Kazmi,W.W.;Min,G.H.;Haider,J.;Nam,S.;Baek,I.H.,Facilely synthesized M-montmorillonite(M=Cr,Fe,and Co)as efficientcatalystsfor enhancing CO2 desorption from aminesolution.Ind.Eng.Chem.Res.2021,60,13318-13325.

[0088] [8]Zhang,X.;Liu,H.;Liang,Z.;Idem R.;Tontiwachwuthikul P.;Al-MarriM.J.;Benamor A.,Reducing energy consumption of CO2 desorption in CO2-loadedaqueous amine solution using Al2O3 / HZSM-5 bifunctionalcatalysts.Appl.Energy.2018,229,562-576.

[0089] [9]Zhang,X.;Zhang,X.;Liu,H.;Li,W.;Xiao,M.;Gao,H.;Liang,Z.,Reductionof energy requirement of CO2 desorption from a rich CO2-loaded MEAsolution byusing solid acid catalysts.Appl.Energy.2017,202,673-684.

[0090]

[10] Y. Li, Z. Chen, B. Yuan, L.

[0091]

[11] Q.Sun, T.Li, Y.Mao, H.Gao, T.Sema, S.Wang, L.Liu, Z.Liang, Reducing heatduty of MEA regeneration using a sulfonic acid-functionalized mesoporous MCM-41catalyst, Industrial&Engineering Chemistry Research, 60(2021)18304-18315.

[0092] It can be seen from Table 1 that the nickel-based nitrogen-doped carbon material Ni / NC-600 prepared by the present invention greatly improves the CO2 desorption rate at 90°C and achieves the optimal desorption effect with a relatively small addition amount.

[0093] The present invention forms a stable coordination structure with nickel through highly dispersed nitrogen atoms on the surface of the carbon layer. The coordination structure regulates the electronegativity of the metal site, improves the structure of the catalyst, increases the content and strength of B acid and L acid on the surface of the material, realizes the directional control of the CO2 desorption reaction in the alcohol amine absorption system, and enhances the tolerance of the catalyst to high temperature and strong alkaline environment, thereby improving the operating life of the catalyst. The present invention can stabilize the CO2 desorption temperature of the traditional alcohol amine absorption process at 90-110°C, reduce the desorption energy consumption to below 2.0GJ / tCO2, reduce the degradation loss of alcohol amine, optimize the CO2 capture and regeneration process, and achieve the goal of reducing capture energy consumption and improving capture efficiency.

[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a nickel-based nitrogen-doped carbon material, comprising the following steps: The nitrogen-containing carbon source, the nickel source and water are mixed, and after solid-liquid separation, a composite is obtained; The composite is calcined to obtain a nickel-based nitrogen-doped carbon material.

2. The preparation method according to claim 1, characterized in that: The nitrogen-containing carbon source includes a nitrogen-containing organic polymer.

3. The preparation method according to claim 2, characterized in that: The nitrogen-containing carbon source includes a product formed by 2,4,6-triformylphloroglucinol and 4-nitro-1,3-phenylenediamine, a product formed by trimesaldehyde and metaphenylenediamine, or a product formed by melamine and cyanuric acid.

4. The preparation method according to claim 1, characterized in that: The nickel source is a nickel salt.

5. The preparation method according to claim 1, characterized in that: The calcination temperature is 500-700° C., and the heat preservation time is 2-4 hours.

6. The preparation method according to claim 1 or 5, characterized in that: The calcination is carried out under a protective atmosphere.

7. The nickel-based nitrogen-doped carbon material prepared by the preparation method according to any one of claims 1 to 6.

8. Application of the nickel-based nitrogen-doped carbon material according to claim 7 in the field of catalysis.

9. Use of the nickel-based nitrogen-doped carbon material according to claim 7 in catalytic carbon dioxide desorption.

10. The use according to claim 9, characterized in that: The desorption temperature is 90-110°C.